Pengaruh Harga dan Kualitas Pelayanan Terhadap Loyalitas Pasien Melalui Kepuasan Pasien Sebagai Variabel Intervening - Sari N, Anisa Sasmita; Arsyad, Annisa Wahyuni (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to determine the effect of price and service quality on patient loyalty through patient satisfaction as an intervening variable in patients of the NN Dental Care Muara Jawa Clinic. This study uses a quantitative approach using an empirical research method. The population of this study were patients of the NN Dental Care Clinic located in the Muara Jawa District area, while the sample used was 100 respondents in the age range of 20-45 years. In this study, sampling used the non-probability sampling method, especially the purposive sampling approach method. In this study, the data collection technique used was a questionnaire in the form of a google form link. The data that has been collected was then processed using the SmartPLS 3.2.9 analysis tool with the Structural Equation Modeling (SEM)-PLS method. The results of the study showed that there was a positive and significant effect on price and service quality on patient satisfaction. However, price has a positive but not significant effect on patient loyalty. And service quality shows a positive and significant effect on patient loyalty. Based on the results of the specific indirect effect, patient satisfaction successfully mediates positively and significantly the effect of price and service quality on patient loyalty.